Pituitary carcinoma - case series and review of the literature - Du Four, Stephanie; Van Der Veken, Jorn; Duerinck, Johnny; Vermeulen, Elle; Andreescu, Corina E.; Bruneau, Michael; Neyns, Bart; Velthoven, Van; Velkeniers, Brigitte (Frontiers in Endocrinology, 2022)
Although pituitary adenomas (PAs) account for 15% of intracranial tumors, pituitary carcinomas (PCs) are a rare entity. Most commonly, PCs evolve from aggressive PAs invading the surrounding structures and eventually leading to metastatic lesions. Due to the low incidence, the diagnosis and treatment remains challenging. We report a case series of five patients with pituitary carcinoma (PC) treated in our center. At first diagnosis 3 patients had an ACTH-producing adenoma, 1 a prolactinoma and 1 a double secreting adenoma (GH and prolactin). The mean time interval from initial diagnosis to diagnosis of PC was 10.7 years (range 5-20 years). All patients underwent multiple surgical resections and radiotherapy. Four patients were treated with temozolomide for metastatic disease. One patient with concomitant radiochemotherapy for local recurrence. Temozolomide led to a stable disease in 2 patients. One patient had a progressive disease after 9 cycles of temozolomide. In absence of standard treatment, immunotherapy was initiated, resulting in a stable disease. We report five cases of PCs. Three patients obtained a stable disease after tailored multidisciplinary treatment. Additionally, one patient was treated with immunotherapy, opening a new treatment option in PCs. Overall, PCs are rare intracranial neoplasms occurring several years after the initial diagnosis of aggressive PAs. Currently, the absence of predictive factors for an aggressive clinical course, provokes a challenging management.